The effect of adjuvant chemotherapy on survival in node negative colorectal cancer with or without perineural invasion: a systematic review and meta-analysis - Ying, Hongan; Shao, Jinfan; Liao, Nansheng; Xu, Xijuan; Yu, Wenfeng; Hong, Weiwen (Frontiers in Surgery, 2023)
Purpose: It was aimed at assessing the benefits of adjuvant chemotherapy (ACT) for patients with node-negative colorectal cancer (CRC) either with or without perineural invasion (PNI).We systematically searched PubMed, Cochrane Library, Embase, and Web of Science from database inception through October 1, 2023. Survival outcomes were analyzed using hazard ratios (HRs) and corresponding 95% confidence intervals (CIs).The methodological quality of included studies was assessed using the Newcastle-Ottawa Scale (NOS). Heterogeneity for the descriptive meta-analyses was quantified using the I 2 statistic.Results: Ten studies included in this review. ACT improved overall survival (OS) (HR 0.52, 95% CI 0.40-0.69) and disease-free survival (DFS) (HR 0.53, 95% CI 0.35-0.82) in PNI+ patients but did not affect DFS (HR 1.13, 95% CI 0.72-1.77) in PNIpatients. A disease-specific survival (DSS) benefit with chemotherapy was observed in PNI+ (HR 0.76, 95% CI 0.58-0.99) and PNI-patients (HR 0.76, 95% CI 0.57-1.00).And PNI decreased DFS (HR 1.94, 95% CI 1.52-2.47) and OS (HR 1.75, 95% CI 0.96-3.17) in node-negative CRC.In conclusion, chemotherapy appears most beneficial for survival outcomes in node-negative patients with PNI, but may also confer some advantage in those without PNI.